2009
DOI: 10.1099/vir.0.012955-0
|View full text |Cite
|
Sign up to set email alerts
|

Diverse circovirus-like genome architectures revealed by environmental metagenomics

Abstract: Single-stranded DNA (ssDNA) viruses with circular genomes are the smallest viruses known to infect eukaryotes. The present study identified 10 novel genomes similar to ssDNA circoviruses through data-mining of public viral metagenomes. The metagenomic libraries included samples from reclaimed water and three different marine environments (Chesapeake Bay, British Columbia coastal waters and Sargasso Sea). All the genomes have similarities to the replication (Rep) protein of circoviruses; however, only half have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
163
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 49 publications
2
163
0
Order By: Relevance
“…About 1.6% of the total sequences were homologous to the genus Gokushovirus from the Microviridae. Previous studies found that viruses in the Circoviridae and Microviridae (Gokushovirus) are widespread in marine and fresh waters (Angly et al, 2006;Rosario et al, 2009). As well, some aquatic circovirus-like sequences appear to encode a capsid protein known previously only in RNA viruses (Diemer and Stedman, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About 1.6% of the total sequences were homologous to the genus Gokushovirus from the Microviridae. Previous studies found that viruses in the Circoviridae and Microviridae (Gokushovirus) are widespread in marine and fresh waters (Angly et al, 2006;Rosario et al, 2009). As well, some aquatic circovirus-like sequences appear to encode a capsid protein known previously only in RNA viruses (Diemer and Stedman, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Feature frequency profiles and network representation BLAST was used to compare the complete circular genomes with those from the NCBI database, including sequenced isolates infecting plants, animals and bacteria, as well as environmental genomes from other metagenomic libraries (10 circovirus-like genomes from an Antarctic lake (Ló pez-Bueno et al, 2009), 9 from marine environments (Rosario et al, 2009) and 11 cycloviruses from chimpanzee stools (Li et al, 2010)). Only the NCBI genomes that were similar to at least one environmental genome were kept for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at this time, the number of marine ssDNA viruses that have been cultured in the laboratory is extremely limited. Metagenomic studies including a multiple displacement amplification step, which is known to enrich for small, circular, ssDNA genomes (Haible et al, 2006;Kim et al, 2008), have identified numerous sequences from ssDNA viruses (including both phages and eukaryotic viruses) in marine environments (Angly et al, 2006;Wegley et al, 2007;Desnues et al, 2008;Rosario et al, 2009). However, the ecology of the ssDNA viruses identified through metagenomic sequencing is completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these uncultivated viruses are related to members of the bacteriophage family Microviridae 9 , but perhaps even larger number encode RC-Reps displaying phylogenetic affinity to one of three families of eukaryotic ssDNA viruses-Circoviridae, Geminiviridae and Nanoviridae (for example, see refs [24][25][26][27]. Interestingly, instead of encoding genes for corresponding CPs (circo-, gemini-and nano-like), these viruses typically bear open-reading frames that do not share appreciable similarity with sequences in the databases.…”
mentioning
confidence: 99%